Pengembangan Instrumen Penilaian Sikap Untuk Mengungkap Sikap Gotong Royong Siswa SD - Sholekhah, Rita Amelia; Mawardi, Mawardi (Universitas Muhammadiyah Magelang, 2024)
The current use of attitude assessment is not optimal because teachers only observe student behavior without using standard instruments to assess student social attitudes, especially mutual cooperation attitudes. Based on these problems, this research aims to develop an instrument for assessing mutual cooperation attitudes using a Likert Scale. This research uses development (R&D) involving fourth grade elementary school students. Based on the validation test of attitude assessment experts, the score reached 92.8%, included in the very high category. Data analysis techniques use descriptive analysis, percentages and categories. Based on validation tests, language experts produced a score of 76%, included in the high category. Meanwhile, based on validation tests, learning design experts produced a score of 96.5%, included in the very high category. The results of the limited trial showed that of the 30 statement items regarding mutual cooperation attitudes, all items were declared valid with the lowest calculated r value of 0.361. The Pearson Correlation r calculated value was ≥ 0.248, indicating the validity of the instrument. Reliability shows a value of 0.953. Based on this trial, the instrument for assessing mutual cooperation social attitudes was considered valid and reliable, so it is appropriate to be implemented to assess the mutual cooperation attitudes of fourth grade students.